1978
DOI: 10.1111/j.1399-0039.1978.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA System and Affective Disorders: A Sibship Genetic Study

Abstract: The authors have investigated HLA-haplotype zygotic assortment in 21 families with multiple cases of affective disorders and in 19 sibling pairs discordant for the disease. The finding of excess similarity between affected sibs stressed the possibility of the existence of genes in the HLA chromosomal region which are involved in the susceptibility to affective disorders. The mode of inheritance of such an hypothesized DS gene was also tested and some theoretical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Results of this analysis suggested linkage. A sib pair analysis of these data pooled with data from Weitkamp et al (1980, in which bipolar individuals were not included), Targum et al (1979), and Smeraldi (Smeraldi & Bellodi, 1981;Smeraldi et al, 1978) also suggested linkage. More specifically, an analysis of sibships having only two affected members indicated linkage, whereas the analysis of sibships having three or more ill members did not find evidence of linkage.…”
Section: Hla Linkagementioning
confidence: 94%
See 1 more Smart Citation
“…Results of this analysis suggested linkage. A sib pair analysis of these data pooled with data from Weitkamp et al (1980, in which bipolar individuals were not included), Targum et al (1979), and Smeraldi (Smeraldi & Bellodi, 1981;Smeraldi et al, 1978) also suggested linkage. More specifically, an analysis of sibships having only two affected members indicated linkage, whereas the analysis of sibships having three or more ill members did not find evidence of linkage.…”
Section: Hla Linkagementioning
confidence: 94%
“…The affected sib pair method does not allow simple estimation of the recombination fraction, but it does not require assumptions about the mode of inheritance. Smeraldi and colleagues (Smeraldi & Bellodi, 1981; Smeraldi, Negri, Melica, & Scorza-Smeraldi, 1978) examined HLA linkage to affective disorders in 26 families by means of the sib pair method. Illness was defined by RDC for bipolar or unipolar disorders.…”
Section: Linkage Analysesmentioning
confidence: 99%
“…Several such studies have been attempted in MDI, but no conclusive evidence for linkage has been found. With the HLA system, both linkage and association have been reported (Smeraldi et al 1978, Weitkamp et al 1981, Weitkamp & Stancer 1989, Stancer et al 1988. However, a review of 18 such studies did not support the earlier findings (Tsuang & Faraone 1990).…”
mentioning
confidence: 93%
“…Following Green and Woodrow's advice, a large number of investigators apparently only consider for analysis families in which all four parental haplotypes can be identified with certainty (see, for instance, Smeraldi et al 1978). This practice is wasteful since ambiguous sibships contain considerable information.…”
mentioning
confidence: 99%